Efektivitas Arbitrase sebagai Alternatif Penyelesaian Sengketa dalam Kontrak Bisnis Perusahaan Asuransi - Canra Batara Oloan Sinambela (Jurnal Hukum Lex Generalis, 2024)
This study aims to analyze the effectiveness of arbitration as an alternative dispute resolution mechanism in business contracts within the insurance sector in Indonesia. Based on secondary data gathered from various sources, the findings indicate that arbitration offers significant advantages in terms of time and cost compared to litigation in court. However, the implementation of arbitration in the insurance sector still faces challenges, such as a lack of understanding of arbitration procedures, a limited number of arbitrators with specialized expertise in insurance, and difficulties in enforcing arbitration awards. This study recommends the establishment of a dedicated arbitration institution for the insurance sector, improved coordination between arbitration institutions and courts, and efforts to expand insurance companies' understanding of the benefits of arbitration. Thus, arbitration can be a more effective and efficient solution for resolving business contract disputes in the insurance industry.